Design and Validation of a Discipline-Oriented Curriculum Model for Elementary Education with an Emphasis on Gardner\'s Five Minds Approach - Mehzad Alirezaei; Faezeh Nateghi; Mohammad Seifi (Iranian Evolutionary Educational Psychology Journal)
Objective: The aim of this research was to design and validate a discipline-oriented curriculum model for elementary education with an emphasis on Gardner's Five Minds approach. Methods: This study employed a mixed exploratory sequential research method. Initially, the desired model was developed through qualitative methods (synthetic literature review and semi-structured interviews). Subsequently, the proposed model's validity was assessed using quantitative method (survey) with input from the experts. Among the various theoretical and empirical studies conducted in this area, several were analyzed using synthetic literature review. Additionally, semi-structured interviews were conducted with seven experts and scholars in the field of Gardner's Five Minds approach, and their opinions were coded and analyzed to formulate the proposed model. Furthermore, to validate the research's proposed model, a researcher-made questionnaire was administered, completed by 22 experts through purposive sampling. Results: The research findings indicated that the discipline-oriented curriculum based on Gardner's Five Minds for elementary education comprises 8 dimensions and 17 sub-dimensions. These dimensions encompass goals, content, teaching-learning methods, learning opportunities, learning resources, learning environment, learning time, and assessment. Moreover, the results suggested that, from the perspective of experts and scholars in this field, the proposed model in this research enjoys good credibility. Conclusions: Based on the research findings, it can be concluded that Gardner's Five Minds approach is more critical than multiple intelligences, and education based on these approaches can better prepare students for the complex world of the future. Therefore, it is recommended that educational stakeholders consider the proposed model for designing education for elementary school students.